ECONOMIC COST – EFFECTIVENESS OF DIFFERENT NITROGEN APPLICATION IN THE PRODUCTION OF CORN ON CHERNOZEMS SOIL - Živanović, Ljubiša; Kovačević, Vlado; Lukić, Vladan (Economics of Agriculture, 2018)
The aim of this study is to determine the optimum quantity of nitrogen applied in corn production at which maximum proft is achieved. Optimal nitrogen application is important for two main reasons: frst for achieving maximum proftability in the production of maize and other is to avoid environmental pollution as the nitrogen is one of the main polluters. In the three-year period (2005 - 2007) were performed research on the effects of nitrogen quantity (control - without fertilization, PKNfon, PKN60, PKN120 and PKN180) and hybrids of different vegetation length (ZPSC 434 ZPSC ZPSC 578 and 677) on yield and proftability. Increasing application of nitrogen tended to raise grain yield by 9.9 - 13.5%. The lowest average corn grain yield (9.49 t ha-1) was registered with the hybrid ZP 434. It was somewhat higher (9.75 t ha-1) with the hybrid ZP 578 and the highest corn grain yield (10.03 t ha-1) with ZP 677. Study shows that highest yield is not always most proftable. In production year with good water supply (2005) highest proft is achieved with moderate use of nitrogen (60 kg ha-1). In draught production years (2006 and 2007) highest proft was achieved with application of 60 to 120 kg ha-1.